The diagram of the triangle is shown below
One interior angle is 56°
One exterior angle is 103° ⇒ we can work out one interior angle 180°-103° = 77°
The other interior angle is 180° - (56°+77°) = 44°
Answer:
∫ C ( y + e√x) dx + ( 2x + cosy² ) dy = 1/3
Step-by-step explanation: See Annex
Green Theorem establishes:
∫C ( Mdx + Ndy ) = ∫∫R ( δN/dx - δM/dy ) dA
Then
∫ C ( y + e√x) dx + ( 2x + cosy² ) dy
Here
M = 2x + cosy² δM/dy = 1
N = y + e√x δN/dx = 2
δN/dx - δM/dy = 2 - 1 = 1
∫∫(R) dxdy ∫∫ dxdy
Now integration limits ( see Annex)
dy is from x = y² then y = √x to y = x² and for dx
dx is from 0 to 1 then
∫ dy = y | √x ; x² ∫dy = x² - √x
And
∫₀¹ ( x² - √x ) dx = x³/3 - 2/3 √x |₀¹ = 1/3 - 0
∫ C ( y + e√x) dx + ( 2x + cosy² ) dy = 1/3
![{ \qquad\qquad\huge\underline{{\sf Answer}}}](https://tex.z-dn.net/?f=%7B%20%5Cqquad%5Cqquad%5Chuge%5Cunderline%7B%7B%5Csf%20Answer%7D%7D%7D%20)
Equation of line passing through given points :
Let's proceed with two point form ~
![\qquad \sf \dashrightarrow \: y - y1 = \cfrac{y2 - y1}{x2 - x1} (x - x1)](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20y%20-%20y1%20%3D%20%20%5Ccfrac%7By2%20-%20y1%7D%7Bx2%20-%20x1%7D%20%28x%20-%20x1%29)
Assume :
![\qquad \sf \dashrightarrow \: y - 3= \cfrac{3 - 3}{ - 4 - 6} (x - 6)](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20y%20-%203%3D%20%20%5Ccfrac%7B3%20-%203%7D%7B%20-%204%20-%206%7D%20%28x%20-%206%29)
![\qquad \sf \dashrightarrow \: y - 3= \cfrac{0}{ - 10} (x - 6)](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20y%20-%203%3D%20%20%5Ccfrac%7B0%7D%7B%20-%2010%7D%20%28x%20-%206%29)
![\qquad \sf \dashrightarrow \: y - 3 = 0](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20y%20-%203%20%3D%200)
![\qquad \sf \dashrightarrow \: y = 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20y%20%3D%203)
So, the equation of required line is : y = 3 ~
Answer:
= x-
27
y-x-2
y=-3x-24
y=-x+
36
5
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
An exponential function which crosses through (1,3) and (2,9) will have a base of 3 since the y values are multiples of 3.
3^1 = 3
3^2 = 9
This means that the function is y = 3^x.